Efficient CRISPR/Cas9-mediated gene disruption in the tetraploid protist Giardia intestinalis - Horáčková, Vendula; Voleman, Luboš; Hagen, Kari D; Petrů, Markéta; Vinopalová, Martina; Weisz, Filip; Janowicz, Natalia; Marková, Lenka; Motyčková, Alžběta; Najdrová, Vladimíra; Tůmová, Pavla; Dawson, Scott C; et al. (Open biology, 2022)
CRISPR/Cas9-mediated genome editing has become an extremely powerful technique used to modify gene expression in many organisms, including parasitic protists. Giardia intestinalis, a protist parasite that infects approximately 280 million people around the world each year, has been eluding the use of CRISPR/Cas9 to generate knockout cell lines due to its tetraploid genome. In this work, we show the ability of the in vitro assembled CRISPR/Cas9 components to successfully edit the genome of G. intestinalis. The cell line that stably expresses Cas9 in both nuclei of G. intestinalis showed effective recombination of the cassette containing the transcription units for the gRNA and the resistance marker. This highly efficient process led to the removal of all gene copies at once for three independent experimental genes, mem, cwp1 and mlf1. The method was also applicable to incomplete disruption of the essential gene, as evidenced by significantly reduced expression of tom40. Finally, testing the efficiency of Cas9-induced recombination revealed that homologous arms as short as 150 bp can be sufficient to establish a complete knockout cell line in G. intestinalis.
Keywords: gene knockout; Giardia; RNA, Guide, CRISPR-Cas Systems; CRISPR-Cas Systems; vodící RNA, systémy CRISPR-Cas; Gene Editing; CRISPR-Cas systémy; Humans; Giardia lamblia; lidé; editace genu; CRISPR/Cas9; tetraploidie; multiploid; Tetraploidy